Transportation and the belt and road initiative : a paradigm shift - de Loisy, Nicolas (Hong Kong : SCMO Research, 2019)
The Belt and Road Initiative (BRI) has received considerable critical attention from the infrastructure, political and media worlds. Most reports and articles on the subject are confused at best, when they are not completely misinformed or contradictory. To date there has been little agreement on the number of BRI projects, amounts spent, dates, and geographical distribution. A global information warfare campaign of mis-information, disinformation, and intoxication is currently at play about the BRI, which direct result is to confuse the situation even more...
1. Introduction -- 2. Globalization -- 3. Vulnerabilities -- 4. Sea Transportation -- 5. Rail Transportation -- 6. Road Transportation -- 7. Air Transportation -- 8. Pipeline Transportation -- 9. Grid Transportation -- 10. Digital Transportation -- 11. Sustainability -- 12. Governance -- 13. Ambitions -- 14. Conclusion -- 15. Interview -- 16. Statistical Tables -- 17. List of Tables, Photos, Figures and Maps.
Includes bibliographical references and index.
Keywords: TRANSPORTATION -- HANDBOOKS, MANUALS, ETC